2017
DOI: 10.1080/10903127.2017.1356410
|View full text |Cite
|
Sign up to set email alerts
|

Observational Multicenter Study of a Direct-to-CT Protocol for EMS-transported Patients with Suspected Stroke

Abstract: In this sample from seven hospitals, a minimal reduction in door-to-CT-ordered and door-to-CT-started time, but no change in door-to-needle time, was found for EMS patients with suspected stroke taken directly to the CT scanner, compared to those evaluated in the ED prior to CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Training emergency room professionals [ 61 , 62 , 63 , 64 , 65 , 66 ], promotion of specific stroke code protocols [ 30 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ], direct transfer from ambulance to the imaging room [ 86 , 87 , 88 , 89 , 90 , 91 , 92 ], strategic location of the imaging room (IR) [ 93 ], and routine administration of thrombolysis in the IR, were considered effective strategies to reduce thrombolysis delay [ 68 , 69 , 85 , 86 , 87 , 88 , 89 , 94 , 95 ]. In places where the physician, usually a neurologist, responsible for thrombolysis, is on-call, pre-notification of possible stroke before imaging also reduced delays [ 37 , 68 , 69 , 73 , 84 , 85 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Training emergency room professionals [ 61 , 62 , 63 , 64 , 65 , 66 ], promotion of specific stroke code protocols [ 30 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ], direct transfer from ambulance to the imaging room [ 86 , 87 , 88 , 89 , 90 , 91 , 92 ], strategic location of the imaging room (IR) [ 93 ], and routine administration of thrombolysis in the IR, were considered effective strategies to reduce thrombolysis delay [ 68 , 69 , 85 , 86 , 87 , 88 , 89 , 94 , 95 ]. In places where the physician, usually a neurologist, responsible for thrombolysis, is on-call, pre-notification of possible stroke before imaging also reduced delays [ 37 , 68 , 69 , 73 , 84 , 85 ,…”
Section: Resultsmentioning
confidence: 99%
“…Use of ambulance significantly reduced pre and intra-hospital delays, especially if pre-notification is made to the hospital allowing the hospital teams to check the patient’s previous clinical notes and the put everything involved in the chain of care in “preparedness mode” including the availability of the imaging room [ 12 , 15 , 16 , 17 , 20 , 22 , 23 , 37 , 39 , 40 , 44 , 48 , 51 , 61 , 92 , 96 , 97 , 98 , 110 , 111 , 112 , 113 ]. For time-dependent treatment, such as the ART, implementation of prehospital [ 51 , 61 , 75 , 98 , 107 ] and intrahospital [ 48 , 51 , 59 , 67 , 68 , 70 , 71 , 72 , 74 , 76 , 77 , 79 , 84 , 86 , 89 , 90 , 91 , 92 , 108 , 109 , 111 , 114 , 115 , 116 , 117 ] protocols are fundamental. Although methodology and pro...…”
Section: Discussionmentioning
confidence: 99%
“…Kamal et al found a significant reduction in DTN time comparing patient-level routing (patients routed directly to CT compared to patients not routed directly to CT), whereas our study, and that of Cone et al, compared patients treated at hospitals with and without (or before and after) direct-to-CT routing policies. 20,21 Further, the large institutional focus on stroke care that accompanies bundled quality improvement initiatives may have contributed to the measured short-term effects in other studies. Therefore, our results may better represent the effect of these policies in sustained practice.…”
Section: Discussionmentioning
confidence: 99%
“…Our data, however, are consistent with the findings of a recent before-after study of direct-to-CT routing by Cone et al Among 7 regional stroke centers, the authors found no statistically significant difference in DTN times after implementation of direct-to-CT routing policies (42 minutes before and 44 minutes after) and a modest reduction in DTI time of 4 minutes. 21 That study compared patients treated immediately before and after the policy change, such that a learning curve may have diminished differences between groups. However, the results of our study, in which the preponderance of direct-to-CT hospitals were no longer in the policy learning period, support those findings.…”
Section: Discussionmentioning
confidence: 99%
“…While previous guidelines have recommended transporting patients directly from the ambulance to the CT scanner, there may be little added benefit, as this practice was found to have no change in reducing time to stroke treatment. 29 Lab work is not indicated before a CT scan is completed but should include baseline electrolyte, hematologic and renal panels and troponins to look for concomitant MI of cardiac strain. Metaanalysis concludes that CT angiography (CTA) or CT perfusion (CTP) did not increase the risk of kidney injury in stroke patients, or even patients with known kidney disease, thus performing CT before lab work is acceptable.…”
Section: Hospital Arrivalmentioning
confidence: 99%